مساهمة في إيجاد قاعدة بيانات لتقدير جودة مياه بحيرة 16 تشرين - محمد غفر; هيثم شاهين; ضياء محلا (Tishreen University, 2019)
من أجل إيجاد قاعدة بيانات لتقدير العوامل المؤثرة على جودة مياه بحيرة 16 تشرين، تم تنفيذ هذه الدراسة على مدار عام كامل امتد من شهر تشرين الثاني عام  2008م ولغاية شهر تشرين الأول عام2009م، بحيث شملت الدراسة الفصول الأربعة للسنة. جُمعت العينات من بحيرة 16 تشرين بشكل دوري وبصورة شهرية من موقعي مراكب فينوس ونبع الصفصاف، وبعد إنجاز بعض القياسات الحقلية في الموقع كدرجة الحرارة ودرجة الحموضة، تمت تهيئة العينات المائية ليصار إلى تحديد حمولتها الكاتيونية وحمولتها الأنيونية باستخدام تقانة الـIC (الكروماتوغرافيا الأيونية) . تشير نتائج هذا البحث إلى تراوح درجات الحرارة في موقعي الدراسة ضمن المجال (11-25.8) درجة مئوية بما يتوافق مع تغيرات درجات الحرارة مع التغيرات الفصلية. كما تظهر نتائج هذا البحث ثباتية درجات الحموضة في موقعي الدراسة على امتداد فصول السنة، إذ تراوحت ضمن المجال (7.32-8.28) مما يدل على عدم تعرض مياه البحيرة لمؤثرات خارجية حامضية كانت أم قلوية. هذا من جهة، من جهة ثانية، وفيما يتعلق بالحمولة الأنيونية، المتمثلة بالمحتوى الفوسفاتي و الأزوتي، تشير نتائج هذا البحث إلى بقاء مياه البحيرة بعيدة جداً عن ظاهرة الإثراء الغذائي، إذ تراوح تركيز شاردة الفوسفات ( ) ضمن المجالmg/l [0.21-0.45]، في حين تراوح تركيز شاردة النترات ( ) ضمن المجالmg/l [1.82- 4.70]. In order to create a database to estimate the factors influencing the quality of the waters of 16 Tishreen Lake, this study has been implemented over the full year extended from November 2008 until October 2009, so the study included the four seasons of the year. Samples were collected from 16 Tishreen Lake periodically and on a monthly basis from boats Venus and Al-Safsaf spring. After the completion of some field measurements at the site such as the temperature and PH, water samples has been made to be set tonnage of cationic and cargo anionic using the technology of the IC  (Ion Chromatography). The results of this research are to indicate varying the temperature in the study sites ranged from (11-25.8) C0 in accordance with temperature changes with seasonal changes. The results of this research show Stability degrees of acidity in the study sites along the seasons of the year, with a range within the domain (7.32-8.28), which indicates that the water of the lake is not exposed to external effects, acidic or alkaline. On the other hand, and with regard to the cargo anionic, which is full of phosphate and nitrogen, the results of this research indicate that the lake is very far from the phenomenon of Eutrophication, with a range concentration of phosphate anion ( ) within the domain [0.21-0.45] mg/l, whereas in nitrate anion concentration ( ) within the domain] 1.82- 4.70  [mg/l.